2019
DOI: 10.1007/s10531-019-01901-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying genetic distance between wild and captive strains of the grey partridge Perdix perdix in France: conservation implications

Abstract: The grey partridge Perdix perdix is an important gamebird in Europe. Its numbers have decreased dramatically during the XXth century and releases are commonly undertaken for the conservation of the populations and/or hunting purposes in Western Europe. However, this practice that generally involves birds from commercial farms raises several concerns, among which a potential hybridization between farmed and wild individuals. Herein, based on microsatellite markers, we characterize the genetic patterns of farmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The spread of allochthonous genotypes from artificially translocated or farm-reared partridges into conspecifics or congeneric wild populations is a known pattern already found in several previous analyses [15,16,18,40,41,44,[58][59][60]. Consistent with these results, we found haplotypes of the allochthonous A. chukar in Italian A. graeca (Table S1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The spread of allochthonous genotypes from artificially translocated or farm-reared partridges into conspecifics or congeneric wild populations is a known pattern already found in several previous analyses [15,16,18,40,41,44,[58][59][60]. Consistent with these results, we found haplotypes of the allochthonous A. chukar in Italian A. graeca (Table S1).…”
Section: Discussionsupporting
confidence: 90%
“…In our case study, the spread of allochthonous genotypes from farm to wild birds, which was already highlighted as a potential problem for species management and conservation [ 18 , 58 ] does not seem to be the major driver of mismatches between morphology and DNA taxonomy in Italian partridges. Indeed, we found hybridization and introgression of genotypes between genera more frequently in samples from museums and collections (52.4%) and in wild birds (5.78%) than in farm-reared birds (0.1%).…”
Section: Discussionmentioning
confidence: 89%
“…When traumatic mortalities are investigated in avian species, most of the studies focus on gross lesions, and little is mentioned about complementary studies that may provide information about survival after the initial trauma [2][3][4][5][6]26,27]. In one study, the authors determined that 36% of whooping cranes (Grus americana) that collide with overhead lines survived the trauma [27], whereas Bech et al (2012) [35] demonstrated that rock ptarmigan hen (Lagopus muta) can fly up to 600 m after collision. In our cases, the histopathology, immunohistochemistry, and entomology support that 44,4% (n=4) of animals survived the trauma but died shortly after due to internal bleeding, following an uncertain period ranging from few minutes to hours (even days, such as in case 5).…”
Section: Discussionmentioning
confidence: 99%
“…The current populations, at least in Western Europe, are composed by a mixture of wild and farmed individuals that are released for conservation or hunting purposes. This aspect influenced boththe genetic diversity of the species, as the released individuals hybridize with the wild ones with a high risk of genetic introgressions, and the natural distribution of the species, due to the release of these commercial individuals in areas outside their "natural" climate envelope 69 , 70 . In addition, as this species nests on the ground in grasslands, it suffered massive declines during the XXth century due to habitat loss and degradation caused by agricultural intensification.…”
Section: Discussionmentioning
confidence: 99%